UBB expansion plan: Spain - Sousa, André Henderson (2015)
Just like the Portuguese saying “who runs for fun does not get tired”. UBB, a textile merchandising brand for Universities has been founded by four friends in 2012. It all started when Rui and André noticed that in their university there was no official merchandising. They saw a window of opportunity of bringing something new to the fore, which was an alternative for universities to have an official merchandising line without any monetary investment. Since then UBB has been able to partner up with 6 Universities and 2 organization related to university students. Cool and with minimal design, associated with good customer service, good quality products, a consignment model (a different way of operating in this market) and passion for what they do has been the main drivers of UBB’s success. This venture has been successful in Portugal. However, Portugal is a small market for a clothing brand to be sustainable so the team has decided to start the internationalization process. The chosen country for expansion is Spain because it is the closest country, with a much larger market, and it is a door for further expansion. Based on the study conducted for Spain’s expansion, we can conclude that there is an opportunity to grow and become sustainable in a foreign country. All the assumptions were based on past experience.